Accelerating the understanding of Aspergillus terreus: Epidemiology, physiology, immunology and advances - Raman Thakur; Sonia Kumari Shishodia; Ananya Sharma; Arjun Chauhan; Sumanpreet Kaur; Jata Shankar (Current Research in Microbial Sciences, 2024)
Aspergillus species encompass a variety of infections, ranging from invasive aspergillosis to allergic conditions, contingent upon the immune status of the host. In this spectrum, Aspergillus terreus stands out due to its emergence as a notable pathogen and its intrinsic resistance to amphotericin-B. The significance of Aspergillus-associated infections has witnessed a marked increase in the past few decades, particularly with the increasing number of immunocompromised individuals. The exploration of epidemiology, morphological transitions, immunopathology, and novel treatment approaches such as new antifungal drugs (PC945, olorofim) and combinational therapy using antifungal drugs and phytochemicals (Phytochemicals: quercetin, shikonin, artemisinin), also using immunotherapies to modulate immune response has resulted in better outcomes. Furthermore, in the context COVID-19 era and its aftermath, fungal infections have emerged as a substantial challenge for both immunocompromised and immunocompetent individuals. This is attributed to the use of immune-suppressing therapies during COVID-19 infections and the increase in transplant cases. Consequently, this review aims to provide an updated overview encompassing the epidemiology, germination events, immunopathology, and novel drug treatment strategies against Aspergillus terreus-associated infections.